Modeling the System of Beliefs That Affect Driving Under the Influence of Cannabis and Alcohol in Washington State - Scott, Brandon G. (Journal of drug issues, 2021)
Washington state has observed increases in polydrug use in fatal crashes, primarily involving the combination of cannabis and alcohol. The purpose of this article is to explore the belief system associated with driving under the influence of cannabis and alcohol (DUICA) in Washington state using structural equation modeling (SEM). A convenience sample (n = 737) of surveys collected from adults in Washington state was analyzed using SEM to reveal the latent structure of the belief system associated with DUICA. The results of this analysis indicated that the reported DUICA behavior (frequency) was predicted by intention and willingness. Willingness also predicted intention. Intention and willingness were predicted by positive attitudes toward DUICA, as well as normative perceptions that it was acceptable to important people and common behavior for most people. These components were themselves predicted by corresponding beliefs (behavioral beliefs, normative beliefs, and control beliefs). Finally, these beliefs were also influenced by the values that were most important to the respondents. Based on these results, it is reasonable to speculate that strategies to change these beliefs may also reduce DUICA behavior and associated fatal crashes.